Clonal heterogeneity and rates of specific chromosome gains are risk predictors in childhood high‐hyperdiploid B‐cell acute lymphoblastic leukemia. Issue 16 (19th July 2022) - Ramos‐Muntada, Mireia; Trincado, Juan L.; Blanco, Joan; Bueno, Clara; Rodríguez‐Cortez, Virginia C.; Bataller, Alex; López‐Millán, Belén; Schwab, Claire; Ortega, Margarita; Velasco, Pablo; Blanco, Maria L.; Nomdedeu, Josep; et al.
Abstract : B‐cell acute lymphoblastic leukemia (B‐ALL) is the commonest childhood cancer. High hyperdiploidy (HHD) identifies the most frequent cytogenetic subgroup in childhood B‐ALL. Although hyperdiploidy represents an important prognostic factor in childhood B‐ALL, the specific chromosome gains with prognostic value in HHD‐B‐ALL remain controversial, and the current knowledge about the hierarchy of chromosome gains, clonal heterogeneity and chromosomal instability in HHD‐B‐ALL remains very limited. We applied automated sequential‐iFISH coupled with single‐cell computational modeling to identify the specific chromosomal gains of the eight typically gained chromosomes in a large cohort of 72 primary diagnostic (DX, n = 62) and matched relapse (REL, n = 10) samples from HHD‐B‐ALL patients with either favorable or unfavorable clinical outcome in order to characterize the clonal heterogeneity, specific chromosome gains and clonal evolution. Our data show a high degree of clonal heterogeneity and a hierarchical order of chromosome gains in DX samples of HHD‐B‐ALL. The rates of specific chromosome gains and clonal heterogeneity found in DX samples differ between HHD‐B‐ALL patients with favorable or unfavorable clinical outcome. In fact, our comprehensive analyses at DX using a computationally defined risk predictor revealed low levels of trisomies +18+10 and low levels of clonal heterogeneity as robust relapse risk factors in minimal residual disease (MRD)‐negative childhood HHD‐B‐ALL patients: relapse‐free survival beyond 5 years: 22.1% versus 87.9%, P < 0.0001 and 33.3% versus 80%, P < 0.0001, respectively. Moreover, longitudinal analysis of matched DX‐REL HHD‐B‐ALL samples revealed distinct patterns of clonal evolution at relapse. Our study offers a reliable prognostic sub‐stratification of pediatric MRD‐negative HHD‐B‐ALL patients. Abstract : Automated sequential‐iFISH coupled with single‐cell computational modeling in high‐hyperdiploid (HHD) B‐ALL samples revealed low levels of trisomies 18, 10 and clonal heterogeneity at diagnosis as robust predictive risk factors, properly classifying 85% of patients according to relapse risk. We propose a simple and reliable protocol for improving patient stratification at diagnosis easily applicable into the clinical routine of hematoncology laboratories.